Recombinant activated factor VII as treatment for uncontrolled mucosal haemorrhage. (30th June 2011) - Gracia, J; Prieto, I
Abstract : We report the use of a haemostatic drug (recombinant activated factor VII (rFVIIa)) in a patient who presented a slow but constant bleed in oesophageal mucosa (which required frequent red blood cell transfusion) due to ingestion of caustic products. The administration of rFVIIa ceased bleeding and allowed mucosal cicatrisation and patient haemodynamic stabilisation and clinical recovery.